Specific pulmonary responses during the cycle-run succession in triathletes - Hue, O.; Le Gallais, D.; Prefaut, C. (Scandinavian Journal of Medicine & Science in Sports, 2001)
The aim of the present study was to investigate the relationship between alterations in pulmonary function (i.e., diffusing capacity for carbon monoxide and pulmonary volumes) and the ventilatory response elicited during the cycle-run succession in triathletes. Ten well-trained triathletes performed three exercises: 1) 30 min cycling plus 20 min of running, termed the cycle-run succession; 2) 30 min cycling; and 3) 20 min running. Before and 10 min after each trial, the triathletes underwent pulmonary function testing, including spirometry and diffusing capacity for carbon monoxide. During all trials, ventilatory data were collected every minute using an automated breath-by-breath system. The ventilatory response was significantly higher in the run subsequent to cycling as compared with the run performed independently (P<0.001). There was no change in pulmonary volumes before and after exercises; however, the diffusing capacity for carbon monoxide and the transfer coefficient were similarly decreased (P<0.05) after cycling and the cycle-run succession, but not decreased after running. The increase in minute ventilation in the run segment of the cycle-run succession versus in running alone was significantly correlated with the decrease in diffusing capacity for carbon monoxide measured after versus before the cycle-run succession (P<0.01). This same increase in ventilation was also correlated with the decrease in diffusing capacity measured after the cycle-run succession versus after cycling alone (P<0.03). These results suggest the possibility that the DLCO decrease contributes in part to the ventilatory increase noted in the run after cycling during the cycle-run succession of the triathlon.